ANALISIS PRODUKSI DAN PENDAPATAN PETANI ARAK PASCA PERGUB BALI TAHUN 2020 - Pratiwi, Ida Ayu Meisthya; Yasa, I Made Putra; Sugiri, I Ketut; Kawi, Grace Febby Vallenia; Artika, Regina Tri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.02.TAHUN.2025, 2025)
Balinese arak, a key commodity of Karangasem Regency, serves as a vital livelihood for many farmers but faces challenges in production sustainability and income stability. To address this, the Bali Provincial Government issued Pergub No. 1 of 2020 on the Management of Typical Balinese Fermented Beverages. This study examines the direct impact of labor, education, working capital, land area, and the gubernatorial regulation on arak production and farmers’ income, as well as their indirect impact through production in Eka Tri Buana Village. Using a quantitative approach with path analysis, data sources include primary data from interviews and FGDs, alongside secondary data from relevant institutions. The findings reveal: (1) labor, working capital, and land area significantly boost arak production, while only production volume positively affects farmers’ income; (2) labor, working capital, and land area indirectly influence income through production; (3) the gubernatorial regulation positively impacts the industry but does not directly or indirectly enhance farmers’ income. FGD results indicate that while the regulation strengthens industry productivity, its benefits for farmers as primary producers remain limited. Thus, a holistic policy framework is essential, ensuring support across the entire supply chain, from upstream to downstream to secure the long-term sustainability of the Balinese arak industry.